A new record of the species Haplophthalmus movilae Gruia & Giurginca, 1998 (Isopoda, Oniscidea, Trichoniscidae, Haplophthalminae) - ANDREI GIURGINCA (Travaux de l'Institut de Speologie Emile Racovitza, 2024)
The species Haplophthalmus movilae, long considered as restricted to the sulfidic groundwater ecosystem of Movile Cave was collected from an endogeous location outside the cave. This outlines the endogeous origin of the four species of Oniscidea inhabiting Movile Cave and possible movement of certain species between this cave and other ecosystems